Thursday
March 30, 2017

Post a New Question

Posted by on .

Is this right?!

G(x)=x^3+2 ; x=-2.-1.0,1,2

g(-2) ; -2^3+2=-6
g(-1) ; -1^3+2=1
g(0) ; 0^3+2=2
g(1) ; 1^3+2=3
g(2) ; 2^3+2=10

  • Algebra2 - ,

    looks good to me.

  • Algebra2 - ,

    Thanks very much!

  • Algebra2 - ,

    just a note you should write

    g(-2) = (-2)^3+2 = -6

    you are correct only because (-2)^3 = -2^3

    for even powers, such as 2, (-2)^2 ≠ -2^2

  • Algebra2 - ,

    Lol. Ahh yes I know. I found that mistake. and corrected it too.
    Thank you though.

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question